Study of the Specificities of Thinking in Chemistry Education within the Science Education Cluster - Husna, Nisyya Syarifatul; Hernani, Hernani; Mudzakir, Ahmad (Postgraduate, University of Mataram, 2023)
The aim of this research is to explore the concept of systems thinking in relation to the specificities of systems thinking in science education by conducting a content analysis of studies published between 2010 and 2020. Most of the articles were published between 2017 and 2019. This study employs a descriptive content analysis method on 40 articles about systems thinking in science, utilizing a literature review of international articles. The instruments used include a content analysis format created by the researcher and two expert researchers. Doubtful data were discussed holistically in relation to the content analysis. The results of the research reveal the specificities of systems thinking within the science field. In the realm of chemistry, a systems-based approach through the integration of green chemistry and systemic synthesis questions has proven effective in enhancing systems thinking skills and awareness of sustainability. The application of molecular sustainability principles in chemistry education can lead students to complex thinking, with an understanding of chemistry linked to various systems such as social, economic, and environmental contexts, fostering a holistic understanding. Integrating systems thinking approaches in science education can enhance students' comprehension of the complexities of the real world and equip them with the necessary skills to address increasingly dynamic and interconnected global challenges. The practical implications of these findings highlight the importance of developing a systems-oriented curriculum to support more comprehensive and integrative learning